The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jar.12704
|View full text |Cite
|
Sign up to set email alerts
|

Exploring enablers and barriers to accessing health services after a fall among people with intellectual disability

Abstract: Background Adults with intellectual disability experience high rates of falls making falls prevention an important health need. The purpose of the study was to seek perspectives of older adults with intellectual disability and their caregivers to (a) explore the experiences of older adults with intellectual disability when seeking healthcare services after a fall and (b) identify enablers and barriers when taking up evidence‐based falls recommendations. Method A qualitative exploratory study was undertaken as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…People with ID experience a number of barriers to accessing preventive health care services compared to the general population[ 21 ], to receiving routine medical care[ 22 ] and accessing mental health services[ 23 ]. The scientific literature cites inadequate training of mental health professionals, organizational barriers, lack of services, and poor quality of services as the main obstacles to accessing appropriate mental health care[ 24 ].…”
Section: Increased Vulnerabilitymentioning
confidence: 99%
“…People with ID experience a number of barriers to accessing preventive health care services compared to the general population[ 21 ], to receiving routine medical care[ 22 ] and accessing mental health services[ 23 ]. The scientific literature cites inadequate training of mental health professionals, organizational barriers, lack of services, and poor quality of services as the main obstacles to accessing appropriate mental health care[ 24 ].…”
Section: Increased Vulnerabilitymentioning
confidence: 99%
“…Two studies explored healthcare professionals' and people with intellectual disabilities' adherence to existing fall‐prevention guidelines (Ho et al, 2020; Pal et al, 2014) and found participants' experiences did not reflect current guidelines of care for the prevention of falls, and that people with intellectual disabilities were not routinely offered access to established falls prevention pathways (Ho et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Medication issues are an identified risk factor for falls in people with intellectual disabilities (Axmon et al, 2018; Chiba et al, 2009; Hale et al, 2007; Hsieh et al, 2012; Schoufour et al, 2015; Wagemans & Cluitmans, 2006). Medication reviews for people with intellectual disabilities who also have co‐morbidities such as epilepsy and who take fall‐risk‐inducing medication (such as anticonvulsants) may form part of an effective falls‐prevention intervention (Ho et al, 2020). However, we found a lack of studies investigating medication management interventions to reduce the risk of falls in people with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations